GENDER DIFFERENCES IN PERCEPTIONS AND ATTITUDES TOWARDS ONLINE SHOPPING IN KANYAKUMARI DISTRICT (International Journal of Food and Nutritional Sciences, 2022)
The rise of online shopping has transformed consumer behavior by offering unparalleled convenience, broader product choices, and competitive pricing. In India, both urban and semi-urban areas are witnessing rapid growth in e-commerce usage, driven by increased internet access and smartphone penetration. This study examines gender-based differences in perceptions and attitudes toward online shopping among consumers in Kanyakumari District, a region where traditional values and digital adoption coexist.Primary data were collected through a structured questionnaire from 150 respondents, and statistical tools like Mean, Standard Deviation, Chi-Square Test, Garrett Ranking Technique, and Friedman’s Test were employed for analysis. The findings reveal that while both men and women demonstrate high levels of awareness regarding online shopping, no significant difference exists between genders in terms of awareness levels. Perceived convenience,